Effects of obesity on the pharmacology of proton pump inhibitors: current understanding and future implications for patient care and research. (2nd January 2023) - Jafri, Farwa; Taylor, Zachary L.; Gonzalez, Daniel; Shakhnovich, Valentina
ABSTRACT: Introduction: In the United States, obesity affects approximately ⅖ adults and ⅕ children, leading to increased risk for comorbidities, like gastroesophageal reflux disease (GERD), treated increasingly with proton pump inhibitors (PPIs). Currently, there are no clinical guidelines to inform PPI dose selection for obesity, with sparse data regarding whether dose augmentation is necessary. Areas Covered: We provide a review of available literature regarding the pharmacokinetics (PK), pharmacodynamics (PD), and/or metabolism of PPIs in children and adults with obesity, as a step toward informing PPI dose selection. Expert Opinion: Published PK data in adults and children are limited to first-generation PPIs and point toward reduced apparent oral drug clearance in obesity, with equipoise regarding obesity impact on drug absorption. Available PD data are sparse, conflicting, and limited to adults. No studies are available to inform the PPI PK→PD relationship in obesity and if/how it differs compared to individuals without obesity. In the absence of data, best practice may be to dose PPIs based on CYP2C19 genotype and lean body weight, so as to avoid systemic overexposure and potential toxicities, while monitoring closely for efficacy.